Clematis wuxiensis (Ranunculaceae), a new species from Chongqing, China - Jiang, Qing-Qing; Deng, Hong-Ping; Qian, Wang; Yang, Zhi-Ming; Zhang, Hua-Yu (Phytotaxa, 2017)
Clematis wuxiensis (Ranunculaceae), a new species from Wuxi, Chongqing, China, is described and illustrated. It is closely similar to both C. montana and C. gracilifolia in having one or several flowers together with leaves arising from axillary buds of old branches, four spreading sepals, glabrous stamens and linear filaments, but differs from them in the usually 2-pinnate leaves with nine leaflets (vs. always ternate or ternate to 1-pinnate with three to five leaflets).